Secure Image Steganography Using Encryption Algorithm - Siti Dhalila, Mohd Satar; Roslinda, Muda; Fatimah, Ghazali; Mustafa, Mamat; Nazirah, Abd Hamid; An, P.K (2016)
The objective of this study is to enhance the confidentiality and security of the image steganography application by combining cryptography algorithm. In this proposed model, the RSA algorithm is used to encrypt a secret message into an unreadable ciphertext before hiding it in the image. Diffie-Hellman algorithm is used to determine the pixel on an image that will be used to store the message. A system based on the proposed algorithm will be implemented using Java and it will be more secured due to double-layer of security mechanisms which are RSA and Diffie-Hellman.